2016
DOI: 10.1021/acs.jpcc.5b10939
|View full text |Cite
|
Sign up to set email alerts
|

Intercalated 2D MoS2 Utilizing a Simulated Sun Assisted Process: Reducing the HER Overpotential

Abstract: Molybdenum disulfide (MoS2) in its two-dimensional (2D) morphology has favorable catalytic properties for the hydrogen evolution reaction (HER). To fully take advantage of this capability and in order to enhance this material’s HER performance, viable methods for synthesizing and tuning electronic properties of 2D MoS2 should be developed. Here, we demonstrate a facile and nonhazardous approach to partially intercalate Li+ ions into the 2D MoS2 host structure. We show that such an intercalation is possible in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 65 publications
(143 reference statements)
1
36
0
Order By: Relevance
“…Confronted with the increasing environmental pollution and exponential consumption of fossil fuels worldwide, clean and renewable energy and their storage devices are urgently sought after . In this regard, lithium‐ion batteries have gained tremendous attention due to its remarkable properties such as large energy density and environmental friendliness .…”
Section: Introductionmentioning
confidence: 99%
“…Confronted with the increasing environmental pollution and exponential consumption of fossil fuels worldwide, clean and renewable energy and their storage devices are urgently sought after . In this regard, lithium‐ion batteries have gained tremendous attention due to its remarkable properties such as large energy density and environmental friendliness .…”
Section: Introductionmentioning
confidence: 99%
“…Lithium ion were partially intercalate into the two dimension molybdenum disulfide for enhanced catalytic properties for the hydrogen evolution reaction [17].…”
Section: Introductionmentioning
confidence: 99%
“…The S vacancies and straining the basal plane of MoS 2 can tune the band structure of MoS 2 , allowing the reduction of the Δ G H . Wang et al demonstrated an approach to intercalate Li + into the 2D MoS 2 , which can tune the band structure of MoS 2 , therefore enhancing the HER activity notably . Nguyen et al employed thiol functionalization to manipulate the electronic structure of MoS 2 flakes, which can be utilized to tune the band alignment of MoS 2 at material interfaces to optimize the operation of catalytic systems .…”
mentioning
confidence: 99%